HUBUNGAN TINGKAT PENGETAHUAN PERAWAT DENGAN PENERAPAN SURGICAL SAFETY CHECKLIST DI KAMAR OPERASI SATU RUMAH SAKIT SWASTA [THE CORRELATION BETWEEN NURSES’ KNOWLEDGE AND THE IMPLEMENTATION OF SURGICAL SAFETY CHECKLIST IN OPERATING THEATER OF ONE PRIVATE HOSPITAL OPERATING] - Yovi Allen; Martina Pakpahan; Martha Octaria (Universitas Pelita Harapan, 2021)
Surgical services in hospitals provide important health services and also part of the patient safety goals. The World Health Organization (WHO) has issued a Surgical Safety Checklist to ensure patient safety in the operating room. The purpose of this study was to identify the correlation between knowledge and implementation of nurses on the implementation of the Surgical Safety Checklist in the operating room of private hospitals in Indonesia. The study used cross sectional design with total sampling. Respondents were 12 nurses in the operating room. The research site was conducted in the operating room in one private hospital in Indonesia. Study used questionner and self-evaluation sheet to collect the data. Questionner for measuring knowledge has cronbach alpha 0.828, while the self evaluation sheet refers to the WHO recommendation. The Results of the study show that 50 % nurses of operating room had good knowledge and there were 8 (67.3%) respondents did the Surgical Safety Checklist in the operating room. Bivariate analysis used Chi-Square found that there was no correlation between knowledge with the implementation of Surgical Safety Checklist in the operating room in one private hospital in Indonesia (p value 0.221). Recommendation for further research may examine other factors related to the implementation of surgical safety checklist.BAHASA INDONESIA Layanan bedah di rumah sakit memberikan layanan kesehatan yang penting dalam keselamatan pasien. Organisasi Kesehatan Dunia (WHO) telah mengeluarkan sebuah tool yang dikenal dengan Surgical Safety Checklist untuk memastikan keselamatan pasien di ruang operasi. Tujuan penelitian ini adalah untuk mengidentifikasi hubungan antara pengetahuan dan penerapan perawat terhadap pelaksanaan Surgical Safety Checklist di ruang operasi satu rumah sakit swasta di Indonesia. Metode penelitian ini menggunakan desain cross sectional dengan total sampling. Responden adalah 12 perawat di ruang operasi. Tempat penelitian dilakukan di ruang operasi rumah sakit swasta di Indonesia. Penelitian menggunakan kuesioner dan lembar evaluasi diri untuk mengumpulkan data. Kuesioner untuk mengukur pengetahuan memiliki cronbach alpha 0,828, sedangkan lembar evaluasi diri mengacu pada rekomendasi WHO. Hasil penelitian menunjukkan bahwa 50% perawat di ruang operasi memiliki pengetahuan yang baik dan 8 (67,3%) responden melakukan penerapan Surgical Safety Checklist di ruang operasi. Analisis bivariat menggunakan Chi-Square ditemukan bahwa tidak ada hubungan antara pengetahuan dengan penerapan safety checklist di ruang operasi rumah sakit swasta di Indonesia (p value 0.221). Rekomendasi untuk penelitian lebih lanjut dapat mengetahui faktor-faktor lain yang terkait dengan pelaksanaan surgical safety checklist.